Revision of Neotropical species of Empididae (Diptera) described by Mario Bezzi. XI. The species described in Empis Linnaeus - Rafael, J. A.; Câmara, J. T. (Zootaxa, 2012)
Bezzi described 11 Neotropical species in Empis Linnaeus, 1758. Eight of them are re-described and illustrated from type and non-type specimens. Currently all re-described species remain in Empis: E. angustipennis Bezzi, 1909, E. chiragra Bezzi, 1909, E. induta Bezzi, 1909, E. leucostigma Bezzi, 1909, E. liodes Bezzi, 1909, E. lucidilabris Bezzi, 1905, E. penniventris Bezzi, 1909 and E. spinifera Bezzi, 1909. The primary or secondary type specimens of these species were examined, (except for E. lucidilabris), and lectotype specimens are here designated for E. angustipennis, E. chiragra and E. spinifera. The type specimens of the remaining three species of Empis described by Bezzi were destroyed.